The illustrated Apocalypse : review and reflection - Chritton, Diane (My University, 1984)
Contents include: early cycles, thirteenth-century apocalypses, the commentaries and the popularity of the illustrated apocalypse.
xii, 200 leaves : ill. ; 28 cm.
Keywords: Bible. N.T. Revelation --Pictorial works.